MANAGEMENT OF ENUCLEATION SURGERY IN MAINE COON CAT: Manajemen Operasi Enukleasi pada Kucing Maine Coon - Syarifuddin, Ahmad; Damhuri, Dedi; Safitri, Jessica Anggun; Wibowo, Sarwo Edy (VITEK : Bidang Kedokteran Hewan, 2024)
Enucleation is a procedure for removing the eye in cats due to pathological conditions that cannot be treated with medical therapy, such as uncontrolled glaucoma or intraocular tumors. Prolapse of the bulbus oculi in cats is generally caused by glaucoma (increased intraocular pressure), bacterial or viral infections, trauma from being hit by a vehicle, scratches or fights with other animals, and eye tumors. The subject of this case was a male cat named Chiko, approximately 1 year old, weighing 2.5 kg, who was brought to the She Wee Veterinary Clinic in Palembang with the complaint of a protruding eye. Based on the anamnesis, physical examination, and clinical symptoms, Chiko was diagnosed with bulbus oculi prolapse and underwent medical treatment in the form of an enucleation surgery. The treatment administered included antibiotics, vitamins, analgesics, and ointments. The use of an Elizabethan collar was also recommended to prevent the wound from being scratched. Recovery showed good wound healing within approximately 7 days without serious complications. It was concluded that the enucleation procedure performed on Chiko, using the transpalpebral technique, had a fausta prognosis. Keywords: Prolapse, Bulbus Oculi, Enucleation, Eye and Cat.